The ecology of plantain squirrel (Callosciurus notatus) at the headquarters of Bako National Park - Chah, Cheng Peng. (Universiti Malaysia Sarawak, (UNIMAS), 2007)
A study of the behaviour, food and population ecology of the Plantain squirrel (Callosiurus notatus), was conducted at the Headquarters of Bako National Park, from 24th November until 3rd December. The study site is consisted of beach forest and riverine forest. The scanning method was used to observe the daily activity of the squirrel and a set of predetermine activity categories were used to record their activity. The study was indicated that the squirrel is active at 0600, 1100 and 1600 hours; and the highest average time spent was on displacement. Though the observation, ten families of the food plants were identified as the squirrels' food resources. The Plantain squirrel (Callosiurlls notatus) is essential as a seed disperser, weeds control and seed predator. A total of 100 traps were at two different trails to estimate the population of the squirrel. The population estimation at Trail 1 and Trail 2 is 36 and 26 individuals respectively. The overall population estimation at the Headquarters of Bako National Park is 56. The hypothesis using Chi-square test shows that there is no significant difference between both trails. The beach forest is the most favourite area to spend foraging but the riverine forest is the rno t suitable area for nesting ground. In general, the food resources are important as it could affect the squirrel behaviour and the population distribution.